Fear conditioning in invertebrates - Pribadi, Amy K.; Chalasani, Sreekanth H. (Frontiers in Behavioral Neuroscience, 2022)
Learning to identify and predict threats is a basic skill that allows animals to avoid harm. Studies in invertebrates like Aplysia californica, Drosophila melanogaster, and Caenorhabditis elegans have revealed that the basic mechanisms of learning and memory are conserved. We will summarize these studies and highlight the common pathways and mechanisms in invertebrate fear-associated behavioral changes. Fear conditioning studies utilizing electric shock in Aplysia and Drosophila have demonstrated that serotonin or dopamine are typically involved in relaying aversive stimuli, leading to changes in intracellular calcium levels and increased presynaptic neurotransmitter release and short-term changes in behavior. Long-term changes in behavior typically require multiple, spaced trials, and involve changes in gene expression. C. elegans studies have demonstrated these basic aversive learning principles as well; however, fear conditioning has yet to be explicitly demonstrated in this model due to stimulus choice. Because predator–prey relationships can be used to study learned fear in a naturalistic context, this review also summarizes what is known about predator-induced behaviors in these three organisms, and their potential applications for future investigations into fear conditioning.